Dinamika Kehidupan Sosial Keluarga Laisa dalam Novel “Dia Adalah Kakakku” Karya Tere Liye - Nanik Wahyuni; Suryani Suryani; Dedy Mardiyansyah (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This research aims to describe the portrait of family life in the novel "Dia is my brother" by Tere Liye, published in 2021. This research is a type of descriptive qualitative research, namely the novel "Dia is my brother" by Tere Liye, while the secondary data source is sociological theory books literature. The data collection technique in this research uses reading and note-taking techniques with a literary sociology approach. The data analysis used in this research is the Miles and Huberman model through three stages, namely data reduction, data presentation and drawing conclusions. The sociological theory of literature says that the main driving factor of all wages is social. The results of this research show that there is a relationship between cooperation and humans as an important factor in the dynamics of social life in the novel "He is my brother".